POPULASI HAMA KEPINDING TANAH (Scotinophara coartata F.) PADA TANAMAN PADI SAWAH DI KECAMATAN DUMOGA UTARA KABUPATEN BOLAANG MONGONDOW - Jandrio H. Moonik; Jantje Pelealu; Henny V.G. Makal; Jimmy Rimbing (Universitas Sam Ratulangi, 2015)
ABSTRACTRice crops (Oryza sativa L.) is a crops that produce rice which is used as staple food of about 90% of Indonesia's population consumes rice. Pest is any organism that can interfere with the growth and development of plants so that the plants become damaged, stunted growth, and or death. Bedbug soil pest (Scotinophara coartata F.) is one of major pests that attacks rice crops and spread on planting rice in Sulawesi, Sumatra, Kalimantan and Java. This research aims to find out pest population S. coarctata in rice plants by plant age in some villages in the sub-district of North Dumoga, regency of Bolaang Mongondow. The research took place in sub-district of North Dumoga, regency of Bolaang Mongondow, which was in three villages, that is North Dondomon, South Mopuya and South Mopuya I, and the execution time was from October to Desember 2014. This research uses survey method with direct observation technique. Each village was taken three observation plot, and determined of five sub observation plot to be observed. The materials and tools used were rice crops planting, meter, plastic rope, bamboo poles, scissors, cameras and stationery. The research result shows that the population of soil bedbug (S. coartata F.) on the rice crops in sub-district of North Dumoga based on the age of the plant, the highest pest population was found in the age 42 hst is 4,15 tails, then in the age 28 hst is 2,81 tails and the lowest in the age 14 hst is 1,35 tails, and based on the location, the highest in the village of South Mopuya ie 3,07 tail, followed by the village of North Dondomon is, 2.67 tails and lowest in the village of South Mopuya I is 2,56 tail.Keyword: rice plants, soil bedbug, population